M1 macrophage predicted efficacy of neoadjuvant camrelizumab combined with chemotherapy vs chemotherapy alone for locally advanced ESCC: A pilot study - Wang, Shu; Xu, Guanghui; Li, Mengbin; Zheng, Jiyang; Wang, Yuhao; Feng, Xiangying; Luo, Jialin; Wang, Shibo; Liu, Huan; Duan, Weiming; Zhang, Hushan; Huang, Depei; et al. (Frontiers in Oncology, 2023)
Introduction The efficacy and safety of immunotherapy have been widely recognized in gastrointestinal-related cancers. However, the efficacy of neoadjuvant camrelizumab for locally advanced esophageal squamous cell carcinoma (ESCC) has not been firmly established. This study compared the efficacy of camrelizumab in combination with neoadjuvant DCF (docetaxel, cisplatin and fluorouracil), with DCF alone for ESCC, and exploring biomarkers related to immune infiltration of the ESCC immunotherapy response. Methods We enrolled and randomly assigned patients with stage II-IVa ESCC to two study treatments: camrelizumab combined with docetaxel, cisplatin and fluorouracil (DCF) regimen and DCF regimen alone. The tissue for multiplex immunofluorescence (mIF) was obtained before and after neoadjuvant therapy. The Response Evaluation Criteria in Solid Tumors RECIST Version 1.1 (RECIST 1.1) and Tumor Regression Grade (TRG) was used to evaluate efficacy. Results A total of 30 patients were enrolled in the study. Following neoadjuvant camrelizumab, the objective response rate (ORR) and the disease control rate (DCR) were 46.7% (7/15) and 95.7% (14/15), respectively. No patients reported complete remission, while ORR and DCR in the chemotherapy group were 26.7% (4/15) and 86.7% (13/15), respectively. R0 resection after neoadjuvant treatment was achieved in 3 out of 15 patients in the combined group and in all patients (15/15) in the chemotherapy group. In the combined group, M1-type tumor-associated macrophages and CD56dim NK cells were more abundant in responders than in non-responders (p < 0.05). A higher M1/M2 ratio was observed in responders (p < 0.05). With respect to the NGS, among the copy number amplified genes, the 11q13 amplicon (CCND1/FGF19/FGF4/FGF3) showed the highest frequency (47%, 7/15). Conclusions Neoadjuvant camrelizumab combined with chemotherapy improved ORR in locally advanced ESCC. M1-type tumor-associated macrophages and CD56dim NK cells might be utilized to predict camrelizumab efficacy.